PROSEDUR PENGUJIAN SUBSTANTIF SALDO KAS DAN BANK OLEH KANTOR AKUNTAN PUBLIK AHMAD RAHARJO UTOMO - Mufid Satrio (2020)
The importance of carrying out substantive tests of cash balances is to signify the fairness of the presentation and disclosure of cash on the balance sheet. The method applied to collect all data by applying a system of interviews with auditors and documentation. Audit process to convince cash and reflect all the company's cash amounts at the balance sheet date and recorded fairly, and to ensure cash has been disclosed and clarified in the financial statements. Substantive testing of cash balances is carried out on one of the companies engaged in the supply of electronic and automotive products. It was concluded that the results of this research were a process of substantive testing of cash and bank balances carried out by Ahmad Raharjo Utomo's Public Accountant Office which had been carried out properly with the auditing standards that were prevalent in Indonesia.